Behavioral Biases of Dealers in U.S. Treasury Auctions - David Goldreich (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper provides evidence of bounded rationality by large dealers in U.S. Treasury auctions. I argue that these dealers use a heuristic of yield-space bidding which leads to biases manifested in three ways: they submit dominated bids, i.e., those that could be improved without raising the bidding price; they bid in a manner that disregards the unevenly spaced price grid; and they round bids in yield space. Consistent with bounded rationality, I show that bidders are less susceptible to bias when the cost of suboptimal bidding is high. While the literature provides substantial evidence of behavioral biases among individual investors, they are less well documented for large sophisticated institutions that are likely to be important for setting asset prices. These primary bond dealers who regularly bid for billions of dollars in Treasury bill auctions are precisely such economic agents.
Keywords: H63; H74; D44; 330; Treasury auctions; Behavioral finance; Staatspapier; Auktion; Anlageverhalten; Begrenzte Rationalität; Schätzung; USA